I think i only get some of it. this is what i did
x = -3 to 4y = 0.3 to 3if we use -3 and 3a < -1 < b
a= -2 to infiniteb= 0 to infinite
Given the triangles ABC and PQR.
Angle A = Angle P
Angle B = Angle Q
Angle C = Angle R
Angle B = 3v+4
Angle Q = 8v-6
Let's find v
3v+4 = 8v-6
-5v = -10
v = 2
Angle B = 3v + 4
Angle B = 3(2) + 4
Angle B = 10.
The correct answer is letter C. 10
Answer:
its so blurry
Step-by-step explanation:
grrrr
Answer:
Step-by-step explanation:
When,x= -1
Now,
f(-1)=-(-1)^2+6
=1+6
=7
Hope it helped you.